The functional differentiation of society and its structural conditions to face the COVID-19 pandemic - Labraña, Julio; Pignuoli Ocampo, Sergio; Thumala- Dockendorff, Daniela; Arnold- Cathalifaud, Marcelo (MAD, 2020)
COVID-19 has produced intense public communication on a global level. Social sciences have reacted by producing information on their impacts in different spheres of social life, particularly regarding economy, politics, and science. However, there has been not so much consideration about how the functionally differentiated structure of society favors or restricts collaborative attempts to address the pandemic. Specifically, in this way, social systems theory will be applied to identify systemic mechanisms of reflection and rationality that could stimulate collaboration, and then propose organizational modes that would foster it.